Periodontitis and Peri-Implantitis Tissue Levels of Treponema denticola-CTLP and its MMP-8 Activating Ability - Petain, Sami (My University, 2022)
Abstract Background and Aims: Chymotrypsin-like-proteinase of Treponema denticola (Td-CTLP) can stimulate the protein expression and activation of matrix metalloproteinase (MMP)-8 (or collagenase-2), a potent tissue destructive enzyme from gingival cells in vitro. The aims of this study were 1) to demonstrate the proMMP-8 (or latent MMP-8) activation by Td-CTLP in vitro and 2) to detect Td-CTLP and MMP-8 protein levels in the tissue samples of peri-implantitis and periodontitis patients. Materials and Methods: proMMP-8 activation by Td-CTLP was analyzed by immunoblots. Tissue specimens were collected from 38 systemically healthy and non-smoking patients; 14 of whom had moderate to severe periodontitis, 10 of whom were suffering from peri-implantitis, and finally 14 of whom showed no sign of periodontal inflammation nor radiological bone decay (control group). The immune-expression levels of MMP-8 and Td-CTLP in the epithelium and the connective tissue were analyzed immunohistochemically. A pixel color-intensity analyze was performed with ImageJ software (version 1.46c; Rasband WS, National Institutes of Health, Bethesda, MD, USA) to obtain a comparable numeral score for each patient’s epithelium and connective tissue MMP-8 and Td-CTLP enzyme level. Results: Td-CTLP activated proMMP-8 in vitro by converting the 70-75 kDa proMMP-8 to 65 kDa active MMP-8. Also, lower molecular size 25-50 kDa parts of MMP-8 were formed. There was no statistically significant difference between the study groups in terms of their MMP-8 and Td-CTLP levels in the epithelium or in the connective tissue. Conclusion: Regarding the limits of this study, it can thus be said that the Td-CTLP enzyme can activate the host proMMP-8 enzyme. Tissue protein levels of MMP-8 and Td-CTLP do not seem to be changed in peri-implantitis and in periodontitis.